Lifespan Changes in the Countermanding Performance of Young and Middle Aged Adult Rats - Beuk, Jonathan; Beninger, Richard J.; Paré, Martin (Frontiers in Aging Neuroscience, 2016)
Inhibitory control can be investigated with the countermanding task, which requires subjects to make a response to a go signal and cancel that response when a stop signal is presented occasionally. Adult humans performing the countermanding task typically exhibit impaired response time, stop signal response time and response accuracy as they get older, but little change in post-error slowing. Rodent models of the countermanding paradigm have been developed recently, yet none have directly examined age-related changes in performance throughout the lifespan. Male Wistar rats (N = 16) were trained to respond to a visual stimulus (go signal) by pressing a lever directly below an illuminated light for food reward, but to countermand the lever press subsequent to a tone (stop signal) that was presented occasionally (25% of trials) at a variable delay. Subjects were tested in 1 hour sessions at approximately 7 and 12 months of age with intermittent training in between. Rats demonstrated longer go trial response time, a higher proportion of go trial errors and performed less total trials at 12, compared to 7 months of age. Consistent stop signal response time and post-error slowing were observed for rats at both ages. These results suggest that the countermanding performance of rats does vary throughout the lifespan, in a manner similar to humans, suggesting that rodents may provide a suitable model for behavioral impairment related to normal aging. These findings also highlight the importance of indicating the age at which rodents are tested in countermanding investigations.